The Influence of Professionalism and Work Discipline on Public Satisfaction Through the Performance of Public Services at the Regional Revenue Agency (BAPENDA) of Tanjung Jabung Barat Regency - Sugianto, Sugianto; Zahari, M.; Sudirman, Sudirman (Dinasti Publisher, 2025)
This study aims to describe work professionalism, work discipline, public service performance, and public satisfaction at the Regional Revenue Agency (BAPENDA) of Tanjung Jabung Barat Regency. It also seeks to examine the influence of professionalism and work discipline on public satisfaction, both directly and indirectly through service performance. The population in this study consists of 118,264 people, with a sample size of 399 respondents. A quantitative approach was used with a survey method, and data were analyzed using Partial Least Squares (PLS). The results of the study indicate that professionalism and work discipline influence public satisfaction, both directly and indirectly through service performance at BAPENDA. This finding suggests that the higher the level of employee professionalism and discipline, the better the quality of service perceived by the public. Indirectly, professionalism and discipline contribute to the improvement of public service performance. Optimal service performance serves as a key bridge in meeting public expectations of government services. When services are delivered effectively, the public experiences tangible benefits from the presence of government officials, which in turn leads to higher levels of satisfaction